Telaah Teoritis: Internalisasi Nilai-Nilai Demokrasi dalam Budaya Sekolah - Sri Hapsari (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2015)
This article provides an theoretical overview of the internalization of democratic values in the school culture. The concept of democratic values in school culture obtained through study of literature. Democratic values considered important for the student as early as possible. Through the school culture, democratic values will be effectively internalized. These value aren’t theoretical, but the values of democratic is implemented in the life of the school with school culture. School culture is interpreted as the norm; value; school rules that are binding on the entire school community. Democratic values that can be applied at schools such as transparency, resolve the issue peacefully, regularly class elections management, acknowledging the diversity in the schools, and so on. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i2.2813